Mortality Amenable to Health Care in 31 OECD Countries Estimates and Methodological Issues - Gay, Juan G.. (OECD Publishing, 2011)
This study assesses the potential of the concept of "mortality amenable to health care" as an indicator of outcome for health care systems. It presents estimates of the mortality amenable to health care in 31 OECD countries for the period 1997-2007. It measures the sensitivity of this indicator to the list of death causes considered to be "amenable to care" by comparing results obtained from two leading lists. It then presents the advantages of this indicator over indicators of general mortality, as well as its limitations
Keywords: Social Issues/Migration/Health